2021
DOI: 10.3390/ijms22084145
|View full text |Cite
|
Sign up to set email alerts
|

Chromeno[3,4-b]xanthones as First-in-Class AChE and Aβ Aggregation Dual-Inhibitors

Abstract: Alzheimer’s disease (AD) is a complex multifactorial disorder, mainly characterized by the progressive loss of memory and cognitive, motor, and functional capacity. The absence of effective therapies available for AD alongside the consecutive failures in the central nervous system (CNS) drug development has been motivating the search for new disease-modifying therapeutic strategies for this disease. To address this issue, the multitarget directed ligands (MTDLs) are emerging as a therapeutic alternative to tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…[15] Many reported anti-aggregation compounds showed interactions with this residue. [35][36][37] Despite this, we must consider that a direct W3-Aβ interaction may be contributing to the inhibition, as reported for other peptides or mini-proteins. Murray et al designed a mini-protein that inhibited Aβ aggregation through protein-protein interactions.…”
Section: In Vitro Ache-induced Aβ Aggregation Assaymentioning
confidence: 98%
“…[15] Many reported anti-aggregation compounds showed interactions with this residue. [35][36][37] Despite this, we must consider that a direct W3-Aβ interaction may be contributing to the inhibition, as reported for other peptides or mini-proteins. Murray et al designed a mini-protein that inhibited Aβ aggregation through protein-protein interactions.…”
Section: In Vitro Ache-induced Aβ Aggregation Assaymentioning
confidence: 98%
“…Nos últimos anos, diversos compostos derivados de xantonas e cromenos naturais e sintéticos têm sido descritos na literatura devido ao seu perfil farmacológico, como potenciais compostos multifuncionais, particularmente para o tratamento da DA [23,24]. Tendo como inspiração o perfil farmacológico interessante deste tipo de compostos e considerando o conceito de compostos multialvo, neste artigo descreve-se o design, a síntese e a avaliação biológica de uma nova família de cromeno [3,4-b]xantonas e dos seus respetivos precursores (E)-2-[2-(propargiloxi)estiril] cromonas, como uma nova classe de inibidores duplos da AChE e agregação Aβ [25].…”
Section: Os Compostos Alvounclassified
“…Malafaia et al 104 reported the design, synthesis, and biological evaluation of a family of 2-styrylchromones as AChE and amyloid-β aggregation dual inhibitors. The authors reported that compound 41 (Scheme 21) was observed to be a well-balanced dual-target inhibitor with an IC 50 value of 3 μM for eeAChE and inhibitory percentage of 66% for amyloid-β aggregation.…”
Section: Chromones With Anti-neurodegenerative Propertiesmentioning
confidence: 99%